Dietary supplementation for female infertility: Recent advances in the nutritional therapy for premature ovarian insufficiency - Han, Qixin; Chen, Zi-Jiang; Du, Yanzhi (Frontiers in Microbiology, 2022)
Premature ovarian insufficiency (POI) ranks top in the reproductive disorders that may impair multiple functioning systems, reduce the quality of life and ultimately deprive patients of their fertility among women. Symptoms can be partially alleviated by present hormone replacement therapy that cannot improve conception or decrease occurrence rates of systemic complication. Nutritional dietary supplements are attracting more and more attention because of their safety, bioavailability, and efficacy for well-being. Nutrients in the daily food are composed of carbohydrates, fat and lipoprotein, protein and polypeptide, vitamins, and vegetable or fruits containing phytoestrogens. These are functional nutrients due to the proliferative, anti-inflammatory, anti-oxidant, and mitochondria-protective potential during the course of menopause. Apart from dietary nutrients, microbe-related nutritional substances, including probiotics, prebiotics and the combination-synbiotics, display high potential as well in supporting estrous cycle, ovarian viability and modulating other vital reproductive functions. The present review will discuss dietary and microbial nutrients and their roles and applications in the living body based upon animal or human research, evaluate possible effect mechanisms from molecular, cellular and tissue levels, and provide insights into nutritional therapy for prolonging reproductive lifespan in female patients.